Safety Elevation for Spa Business Operators After COVID-19 Pandemic in Nakhon Pathom and Phetchaburi Province - Photangtham, Darin; Buajaroen, Hathaichanok; Wisansakunwong, Peeranun; Chankhum, Wariya (Modern Management Frontier Journal, 2024)
This participatory action research aimed to 1) develop the competency and potential for Spa service providers and Spa business operators in Nakhon Pathom and Phetchaburi Provinces and 2) study the approach for proactive preparation in providing Spa business in Nakhon Pathom and Phetchaburi Provinces. The samples were 45 Spa service providers and 5 Spa business operators. The questionnaire was constructed according to SHA. For qualitative data, the instruments were participatory observation; group discussion; in-depth interviews; and workshop. Descriptive statistics were used to analyze quantitative data and content analysis, interpretation, and summarizing causal links were used to analyze qualitative data. The results revealed that 1) self-protection efficacy of Spa service providers against the spread of coronavirus disease 2019 of service providers had the lowest mean score (X=1.30, S.D. 0.56); and 2) the proactive preparation could be achieved through training; the ability development and Spa service provider preparation according to Safety & Health Administration urgently needed to build understanding with Spa business operators. These findings suggested that Spa business operators should make partnership agreement with health facilities or educational institutes to oversee and ensure that the cleanliness and hygiene meet the SHA standards.